10.THE EFFECT OF THE ENZYME REPLACEMENT THERAPY ON THE KIDNEY FUNCTION TESTS AND SERUM ELECTROLYTE LEVELS IN CHILDREN WITH GAUCHER DISEASE (Iraqi Journal of Medical Sciences, 2018)
Background: Gaucher disease (GD) is an inherited autosomal recessive disease. It is most common in the Ashkenazi Jewish population. Many biomarkers might be involved in the etiology, pathogenesis, diagnosis and prognosis of GD in children. Most of them are related to complications due to an involvement of many organs such as liver, spleen and bones by this lysosomal storage disease that caused by a lack of the enzyme glucocerebrosidase.Objective: To investigate the role of kidney function test and electrolytes (urea, creatinine, sodium and potassium) level in the monitoring of the response for the treatment used for patients with GD in follow-up manner.Methods: A case control study was done on 67 children (32 males & 35 females), age range from 2-14 years (mean±SD; 5.3±2.9). The levels of sodium, potassium, urea and creatinine were measured in the samples of patients who were categorized as newly diagnosed untreated patients (n=9), patients receiving enzyme replacement therapy (ERT) for 3-6 months (n=18), 6-12 months (n=20) and patients receiving ERT for more than one year (n=20) and compared with twenty age-matched control subjects (9 males & 11 females) age range from 2-14 years (mean±SD; 5.55±3.05).Results: The data indicated that the level of urea in GD patients (23.39±4.71 mg/dl) was significantly higher than that of age-matched controls (17.5±3.05 mg/dl). Non-significant differences were illustrated in the levels of sodium, potassium and creatinine. Negative significant (p
Keywords: Gaucher disease; macrophage; renal function test; urea; creatinine; sodium; potassium; enzyme replacement therapy; imiglucerase; glucocerebrosidase; glucocerebroside